Heavy-metal enrichment of intermediate He-sdOB stars: The pulsators Feige 46 and LS IV-14°116 revisited - Dorsch, M.; Latour, M.; Heber, Ulrich; Irrgang, Andreas; Charpinet, S.; Jeffery, C. S. (Astronomy & Astrophysics, 2020)
Hot subdwarf stars of spectral types O and B represent a poorly understood phase in the evolution of low-mass stars, in particular of close compact binaries. A variety of phenomena are observed, which make them important tools for several astronomical disciplines. For instance, the richness of oscillations of many subdwarfs are important for asteroseismology. Furthermore, hot subdwarfs are among the most chemically peculiar stars known. Two intermediate He-rich hot subdwarf stars, LS IV-14 degrees 116 and Feige 46, are particularly interesting, because they show extreme enrichments of heavy elements such as Ge, Sr, Y, and Zr, which are strikingly similar in both stars. In addition, both stars show light oscillations at periods incompatible with standard pulsation theory and form the class of V366 Aqr variables. We investigated whether the similar chemical compositions extend to more complete abundance patterns in both stars and validate the pulsations in Feige 46 using its recent TESS light curve. High-resolution optical and near-ultraviolet spectroscopy are combined with non-local thermodynamical-equilibrium model atmospheres and synthetic spectra calculated withTLUSTY andSYNSPEC to consistently determine detailed metal abundance patterns in both stars. Many previously unidentified lines were identified for the first time with transitions originating from GaIII, GeIII-IV, SeIII, KrIII, SrII-III, YIII, ZrIII-IV, and SnIV, most of which have not yet been observed in any star. The abundance patterns of 19 metals in both stars are almost identical, light metals being only slightly more abundant in Feige 46, while Zr, Sn, and Pb are slightly less enhanced compared to LS IV-14 degrees 116. Both abundance patterns are distinctively different from those of normal He-poor hot subdwarfs of a similar temperature. The extreme enrichment in heavy metals of more than 4 dex compared to the Sun is likely the result of strong atmospheric diffusion processes that operate similarly in both stars while their similar patterns of C, N, O, and Ne abundances might provide clues to their as yet unclear evolutionary history. Finally, we find that the periods of the pulsation modes in Feige 46 are stable to better than P less than or similar to 10(-8) s s(-1). This is not compatible with P predicted for pulsations driven by the -mechanism and excited by helium-shell flashes in a star that is evolving, for example, onto the extended horizontal branch.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Stars: abundances; Stars: chemically peculiar; Stars: individual: Feige 46; Stars: individual: LS IV-14°116; Stars: oscillations; Subdwarfs